Structure and organization of two linked ribosomal protein genes in yeast. - Molenaar, C M (1984)
The genes encoding yeast ribosomal proteins rp28 and S16A are linked and occur duplicated in the yeast genome. In both gene pairs the genes are approximately 600 bp apart and are both transcribed in the same direction. Both ribosomal protein genes resemble other ribosomal protein genes studied so far in many structural aspects. The genes are interrupted by an intron near the 5'-end of their coding sequence. In addition the flanking regions contain several conserved sequence elements, which may function in transcription initiation and termination. In agreement with findings concerning other cloned yeast ribosomal protein genes, upstream homology blocks occur that may be involved in coordinate control of ribosomal protein gene transcription. The complete pattern of conserved and diverged sequences between the two duplicate gene pairs is presented.